Factors affecting the adoption of emerging technologies in the Malaysian construction industry - F., Khudzari; R. A., Rahman; S. K., Ayer (IOP Publishing Ltd., 2021)
Technologies are tools or machines that solve real-world problems and, therefore, very important to all industries, including the construction industry. In some parts of the world, technology is a necessity as it helps to improve and increase the efficiency of day-to-day operations, especially in terms of time and budget management. However, there are still many companies that are refusing to apply technology in their construction projects. This study aims to investigate the factors affecting the adoption of emerging technologies in the Malaysian construction industry. To achieve these objectives, this study analyses the extensive interview data with selected construction project managers. Nineteen factors were identified, and these factors can be categorized into two groups (internal; workable by project managers and external; uncontrollable by project managers). This work contributes to the body of knowledge in analysing the factors that affect the adoption of technology in the construction industry from industry practitioners’ angle, which could help researchers and industry practitioners draw up plans to reduce the rejection of technologies among the project managers. The findings of this study could help improve the success of adopting the technologies in any part of the construction industry.